The Botanical Drug PBI-05204, a Supercritical CO2 Extract of Nerium Oleander, Is Synergistic With Radiotherapy in Models of Human Glioblastoma - Colapietro, Alessandro; Yang, Peiying; Rossetti, Alessandra; Mancini, Andrea; Vitale, Flora; Chakraborty, Sharmistha; Martellucci, Stefano; Marampon, Francesco; Mattei, Vincenzo; Gravina, Giovanni Luca; Iorio, Roberto; Newman, Robert A.; et al. (Frontiers in Pharmacology, 2022)
Glioblastoma multiforme (GBM) is the most common as well as one of the most malignant types of brain cancer. Despite progress in development of novel therapies for the treatment of GBM, it remains largely incurable with a poor prognosis and a very low life expectancy. Recent studies have shown that oleandrin, a unique cardiac glycoside from Nerium oleander, as well as a defined extract (PBI-05204) that contains this molecule, inhibit growth of human glioblastoma, and modulate glioblastoma patient-derived stem cell-renewal properties. Here we demonstrate that PBI-05204 treatment leads to an increase in vitro in the sensitivity of GBM cells to radiation in which the main mechanisms are the transition from autophagy to apoptosis, enhanced DNA damage and reduced DNA repair after radiotherapy (RT) administration. The combination of PBI-05204 with RT was associated with reduced tumor progression evidenced by both subcutaneous as well as orthotopic implanted GBM tumors. Collectively, these results reveal that PBI-05204 enhances antitumor activity of RT in preclinical/murine models of human GBM. Given the fact that PBI-05204 has already been examined in Phase I and II clinical trials for cancer patients, its efficacy when combined with standard-of-care radiotherapy regimens in GBM should be explored.